Poor nutrition knowledge amongst caregivers of female footballers at professional club academies in the UK - Roberts, C. (International Journal of Sport Nutrition and Exercise Metabolism, 2025)
The Professional Game Academies (PGA) are young athlete development programmes designed to assist female football players with talent potential transition into professional clubs. Young football players require careful consideration of their dietary intake to support performance, recovery, overall health, growth and maturation, and to reduce injury risk. Dietary habits are multifactorial and are influenced by socioeconomic, educational, cultural, physiological, and environmental factors, and in young athletes also largely determined by caregivers who purchase, provide, and prepare food and meals. The aim of the present study was to quantify nutrition knowledge in the caregivers of PGA athletes. Following ethical approval ninety-two registered caregivers of PGA athletes enrolled in either U15 or U21 academies were invited to participate. General and sport-specific nutrition knowledge was assessed using the Sport Nutrition Knowledge Questionnaire, which has demonstrated construct and content validity, and test-retest reliability (Trakman et al, 2017). Scoring was described as "poor" knowledge (0-49%), "average" knowledge (50-65%), "good" knowledge (66-75%) and "excellent" knowledge (75-100%). Overall nutrition knowledge levels were described as "poor" with a large variance was observed between participants (41 ± 14%). There was no difference between age groups (U15: 43 ± 14%; U21: 39 ± 15%; p = 0.215). These findings are similar to nutrition knowledge reported in caregivers of male academy football players. Greater consideration and investment towards improving nutrition knowledge in caregivers, alongside future research evaluating modes of delivery and the effectiveness of these, is important given the role they play in supporting dietary habits of young female footballers. This may ultimately support optimal dietary intake for health, growth, maturation, performance, recovery, and managing injury risk.